2006
DOI: 10.1002/rcm.2609
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of isoflavones and lignans at trace levels in natural waters and wastewater samples using liquid chromatography/electrospray ionization ion trap mass spectrometry

Abstract: A high-performance liquid chromatography/electrospray ionization ion trap mass spectrometry (HPLC/ESI-MSn) method has been developed for the trace determination of phytoestrogens in aquatic environmental samples. The method includes solid-phase extraction (SPE) and analysis using liquid chromatography/electrospray ionization ion trap mass spectrometry. The aquatic environmental samples, influent of a wastewater treatment plant (WWTP) and creek water, were adjusted to pH approximately 5 before extraction. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
7
35
0
Order By: Relevance
“…In our HPLC-MS/MS analyses, we discovered that the HPLC eluent water contained EL although it had been produced by processing deionised tap water through a water puriWcation system (Saarinen et al 2002b;Smeds and Hakala 2003). Our Wndings on the presence of EL in water were very recently conWrmed in a study by Kang et al (2006). They detected ED and EL in wastewater treatment plant inXuent and in creek water.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…In our HPLC-MS/MS analyses, we discovered that the HPLC eluent water contained EL although it had been produced by processing deionised tap water through a water puriWcation system (Saarinen et al 2002b;Smeds and Hakala 2003). Our Wndings on the presence of EL in water were very recently conWrmed in a study by Kang et al (2006). They detected ED and EL in wastewater treatment plant inXuent and in creek water.…”
Section: Introductionmentioning
confidence: 52%
“…HEL has probably been metabolized from HMR, which is present in cereals, nuts, and oilseeds (Smeds et al 2007). Very recently, the enterolignan content of aquatic environment samples was reported for the Wrst time (Kang et al 2006). The EL concentration was 5 ng/l (0.017 nM) in creek water and 600 ng/l (2.0 nM) in wastewater treatment plant inXuent; both values are about half of the concentrations we found in humic water and in STP inXuent, respectively ( Table 1).…”
Section: Plant Lignans and Enterolignans In Water Sourcesmentioning
confidence: 97%
“…This method was adapted from previous reports [5]. Calibration standards (0, 5, 10, 25, 50 and 100 μg/L) were prepared and analysed in background buffer solutions at each appropriate pH value.…”
Section: Methodsmentioning
confidence: 99%
“…Lundgren and Novak [4] found that the concentration of phytoestrogens in industrial effluent can be much higher (up to 250 μg/L). Genistein, formononetin, biochanin A, daidzein and coumestrol are the most commonly identified phytoestrogens in the aquatic environment, and they have been found in rivers in Australia, Germany and Italy ranging from 1 to 10 ng/L [2,5]. Daidzein and genistein have been detected in river water in Japan at 43 μg/L and 143 μg/L, respectively [6].…”
Section: Introductionmentioning
confidence: 98%
“…However, plant phytoestrogens have been also cited as possible endocrine disruptors in fish along with synthetic hormones and human estrogens from wastewater effluents [8]. Previous studies have found concentrations of biochanin A, daidzein, formononetin, and coumestrol ranging from 1 to 10 ng/L in rivers in Australia, Germany, and Italy [10][11][12][13], whereas 43 mg/L daidzein and 143 mg/L genistein were detected in a Japanese river [8], perhaps because of higher soy impact. Because phytoestrogens are excreted, not only by plants but also by humans and livestock via food consumption, it is important to evaluate their sources in food and their concentration in surface water and wastewater.…”
Section: Introductionmentioning
confidence: 99%